Imaging of Cardiac Valves by Computed Tomography - Gudrun Feuchtner (Scientifica)
This paper describes “how to” examine cardiac valves with computed tomography, the normal, diseased valves, and prosthetic valves. A review of current scientific literature is provided. Firstly, technical basics, “how to” perform and optimize a multislice CT scan and “how to” interpret valves on CT images are outlined. Then, diagnostic imaging of the entire spectrum of specific valvular disease by CT, including prosthetic heart valves, is highlighted. The last part gives a guide “how to” use CT for planning of transcatheter aortic valve implantation (TAVI), an emerging effective treatment option for patients with severe aortic stenosis. A special focus is placed on clinical applications of cardiac CT in the context of valvular disease.